2013
DOI: 10.1177/0003319713506516
|View full text |Cite
|
Sign up to set email alerts
|

Link Between Oxidative Stress and Acute Brain Ischemia

Abstract: The pathogenesis of acute brain ischemia (ABI) is highly complex and involves multiple mechanisms including free radical generation. Imbalance between the cellular production of free radicals and the ability of cells to defend against them is referred to as oxidative stress. Oxidative stress is one of the mechanisms contributing to neuronal damage, potentially induced through the ABI. Through interactions with a large number of molecules, reactive oxygen species may irreversibly destroy or alter the function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 118 publications
(266 reference statements)
1
58
0
2
Order By: Relevance
“…The potential role of oxidative damage as a downstream process in AD pathogenesis has garnered a great deal of interest [164,165]. This interest is mainly because the brain is the most highly oxygen-metabolizing organ in the body; thus, it is highly susceptible to oxidative damage [166][167][168][169][170]. Moreover, the brain has a high lipid content that is prone to oxidation [165,167].…”
Section: Aβ Pathophysiologymentioning
confidence: 99%
“…The potential role of oxidative damage as a downstream process in AD pathogenesis has garnered a great deal of interest [164,165]. This interest is mainly because the brain is the most highly oxygen-metabolizing organ in the body; thus, it is highly susceptible to oxidative damage [166][167][168][169][170]. Moreover, the brain has a high lipid content that is prone to oxidation [165,167].…”
Section: Aβ Pathophysiologymentioning
confidence: 99%
“…A reduced brain damage was observed after ischemia in iNOS knockout mice and the increased expression of iNOS contributes to neuronal injury [43]. In addition, NO increases the formation of free radical and promotes brain damage after stroke by generated iNOS [44]. In this experiment, it showed that the expression of iNOS was increased in the vehicle-treated group compared with the sham-treated group.…”
Section: Discussionmentioning
confidence: 55%
“…23,24 It was shown that, especially superoxide, which formed in the reperfusion phase, combines with nitric oxide and forms peroxynitrite. 25 Love 19 suggested that in transient brain ischemia, free radicals and related reactive chemical species are responsible from the majority of the damage.…”
Section: + Modelmentioning
confidence: 99%